CHARACTERISTICS OF PATIENTS WITH ORGANOPHOSPHORUS POISONING AND ITS MANAGEMENT: PHARMACOEPIDEMIOLOGICAL EVALUATION - KULKARNI, MADHURI; PATIL, ANANT (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to analyze demographics, management pattern, and clinical outcomes in patients with organophosphorus poisoning. Methods: In this subgroup analysis of retrospective data of patients admitted in intensive care unit (ICU) with a diagnosis of acute organophosphorus poisoning, demographic details, pattern of use of medicines, dose of atropine and pralidoxime (PRAM), duration of ICU stay, and clinical outcomes were analyzed. Results: A total of 92 patients with organophosphorus poisoning (mean age 34.7 years; male 69 [75%]) were included. The age of male patients was more than female patients (36.2 vs. 30.0 years; p=0.047). Atropine and PRAM were given to all patients. Ondansetron was used in all patients, whereas ranitidine was used in 91 (98.9%) patients. The mean total dose of atropine in male and female population was 99.5 mg and 89.0 mg, respectively (p=0.298). The mean total dose of PRAM in male and female population was 12.2 mg and 12.0 mg, respectively (p=0.772). There was no difference in the mean (standard deviation) duration of stay in ICU between male patients and female patients (7.6 [4.5] vs. 6.4 [3.9] days; p=0.249). A total of 61 (66.3%) patients were transferred to the ward, whereas 30 (32.6%) died. Conclusion: Atropine and PRAM are the primary drugs for the treatment of organophosphorus poisoning. Ondansetron and ranitidine are useful drugs for the treatment of vomiting and gastric irritation, respectively, in these patients.